Non-compete Agreements: Human Capital Investments or Compensated Wages? - Naomi Kodama; Ryo Kambayashi; Atsuko Izumi (Institute of Labor Economics (IZA), 2025)
Non-Compete Agreements (NCAs) restrict workers from joining or forming rival companies, which impacts labor market dynamics. Theoretical perspectives on NCAs are varied: they can lead to increased employer investment and higher wages by reducing labor turnover, or they might simply raise wages to compensate for the restriction on workers' post-employment choices. Alternatively, NCAs could reduce workers' outside options, leading to unfavorable terms and lower wages. This paper empirically examines the relationship between NCAs and factors such as firm profit, average wages, and training provisions using a firm-level survey in Japan. Estimation results indicate that firms that use NCAs are more likely to invest in their workers, particularly in off-the-job training. In addition, NCAs are positively associated with firm sales, average wages, and labor productivity. These results support the theory that NCAs encourage firms to invest more in their human capital, leading to higher wages and productivity. Our results also align with previous studies on the Japanese labor markets, highlighting the role of employers in investing in human capital. In general, the study adds evidence to the debate on the fairness and economic impact of NCAs.
Keywords: J24; J41; K31; 330; Non-Compete Agreement; wages; human capital investment